3D Printed Tissues: 3D Printed Cartilage‐Like Tissue Constructs with Spatially Controlled Mechanical Properties (Adv. Funct. Mater. 51/2019). (17th December 2019) - de Melo, Bruna A. G.; Jodat, Yasamin A.; Mehrotra, Shreya; Calabrese, Michelle A.; Kamperman, Tom; Mandal, Biman B.; Santana, Maria H. A.; Alsberg, Eben; Leijten, Jeroen; Shin, Su Ryon
Abstract : In article number 1906330, Jeroen Leijten, Su Ryon Shin, and co‐workers develop 3D cartilage‐like tissue through local bioprinting of mesenchymal stem cell spheroids laden with soft and cell stimulating bioink within a mechanically robust hydrogel. This uncoupling of the micro and macro mechanical properties of the 3D printed construct allows it to possess both a chondrogenic microenvironment and the ability to withstand mechanical loads.